Diagnostic and Prognostic Value of Neutrophil Extracellular Trap Levels in Patients With Acute Aortic Dissection - Yang, Shuofei; Xiao, Yongsheng; Du, Yuanfeng; Chen, Jiaquan; Ni, Qihong; Guo, Xiangjiang; Xue, Guanhua; Xie, Xupin (Frontiers in Cardiovascular Medicine, 2022)
Background: Acute aortic dissection (AAD) is a fatal disease demanding prompt diagnosis and proper treatment. There is a lack of serum markers that can effectively assist diagnosis and predict prognosis of AAD patients. Methods: Ninety-six AAD patients were enrolled in this study, and 249 patients with chest pain due to acute myocardial infarction, pulmonary embolism, intramural hematoma, angina or other causes and 80 healthy controls were included as control group and healthy control group. Demographics, biochemical and hematological data and risk factors were recorded as baseline characteristics. The 1-year follow-up data were collected and analyzed. The diagnostic performance and ability to predict disease severity and prognosis of NET components in serum and aortic tissue were evaluated. Results: Circulating NET markers, citH3 (citrullination of histone 3), cell-free DNA (cfDNA) and nucleosomes, had good diagnostic value for AAD, with superior diagnostic performance to D-dimer in discriminating patients with chest pain due to other reasons in the emergency department. Circulating NET marker levels (i.e. citH3, cfDNA and nucleosomes) of AAD patients were significantly higher than that of control group and healthy control group. In addition, circulating NET markers levels were closely associated with the disease severity, in-hospital death and 1-year survival of AAD patients. Systolic blood pressure < 90 mmHg and serum citH3 levels were identified as independent risk factors for 1-year survival of AAD patients. Excessive NET components (i.e. neutrophil elastase and citH3) in the aortic tissue of AAD patient were significantly higher than that of healthy donor aortic tissue. The expression levels of granules and nuclear NET components were significantly higher in aortic tissue from AAD patients than controls. Conclusions: Circulating NET markers, citH3, cfDNA and nucleosomes, have significant diagnostic value and predictive value of disease severity and prognosis of AAD patients. The NETs components may constitute a useful diagnostic and prognostic marker in AAD patients.